The Influence of Senior High School Students Communication on Work Values and Career Interest in the Agriculture Sector - Catur Saputra, M. Haikal; P. Lubis, Djuara; Tri Wibowo, Cahyono (Pusat Publikasi Nusantara, 2023)
The current agricultural development projection requires active participation from the younger generation. However, the declining interest of youth in the agricultural sector poses a challenge to sustainable agricultural development. This research examines communication patterns among high school students with parents, teachers, and peers regarding agricultural work values and interest in the sector. The study analyzed seven variables: individual characteristics (X1), interpersonal communication with parents (X2), teachers (X3), and peers (X4), family characteristics (X5), agricultural work values (Y1), and interest in the sector (Y2). Results show positive relationships between communication with parents, teachers, peers, and agricultural work values. Students perceive agriculture as promising but not fully aligned with their preferences. Teacher communication significantly influences work values and interest more than parents and peers. Effective teacher-student communication is vital in shaping agricultural work values and interest. Bridging perception gaps can boost youth interest in agricultural studies and careers, fostering a skilled and committed future generation for Indonesia's agricultural development